Experimental and theoretical investigations on low temperature EPR of Cu2+ centers in TiO2 rutile single crystal - (:unkn) unknown (ELSEVIER SCIENCE SA, 2017)
We present the results of low-temperature (7-13 K) EPR investigation on Cu2+ doped rutile TiO2 with ion implantation. Spin Hamiltonian containing electronic Zeeman and hyperfine terms was used to analyze experimental data since Cu2+ ions have 1/2 effective spin and their nuclear spin 3/2. The spectra show that there are two equivalent paramagnetic Cu2+ centers and they substitute for Ti4+ ion sites in the TiO2 rutile lattice. Exact diagonalization of spin Hamiltonian is used to analyze EPR spectra, and the small misalignment of sample from the exact crystallographic planes is taken into account. The g tensor values are found as g(x) = 2.1143, g(y) = 2.0907, g(z) = 2.3394 and principal values of hyperfine tensor for Cu-6(2+) are A(x) = 30.6, A(y) = 34.7, A(z) = -93.2 and for Cu-65(2+) A(x) = 33.5, A(y) = 36.7, A(z) = -99.0 (in 10(-4)/cm). (C) 2017 Elsevier B.V. All rights reserved.
Keywords: Cu2+; TiO2; Rutile; EPR; DOPED TIO2; MAGNETIC SEMICONDUCTORS; THIN-FILMS; CO2+; ION